Suplementasi Extra Virgin Olive Oil (EVOO) Pada Ibu Hamil Untuk Mencegah Preeklamsia - Wenny Rahmawati; Dwi Norma Retnaningrum (Universitas Pahlawan Tuanku Tambusai, 2025)
In Indonesia, the leading cause of maternal mortality is still preeclampsia. The Indonesian Health Profile of 2023 recorded 412 cases of preeclampsia as the cause of maternal mortality. Until now, the only way to treat preeclampsia is to terminate the pregnancy. Although the cause of preeclampsia is not yet known, its pathophysiology is characterized by placental hypoperfusion and ischemia. Endothelial dysfunction, inflammatory pathways, the renin-angiotensin system (RAS), and oxidative stress are some of the factors that cause preeclampsia. Antioxidants such as extra virgin olive oil (EVOO) can help reduce oxidative stress. By examining blood pressure, urinary protein, platelets, and monocyte levels, this study attempts to determine the effectiveness of EVOO supplementation in preventing preeclampsia in pregnant women. This quasi-experimental study used a pretest and posttest design with a control group. As many as thirty pregnant women participated in this study, which was divided into treatment and control groups. During the week after delivery, the treatment group was given EVOO daily. The effectiveness of EVOO in preventing preeclampsia will be assessed by analyzing monitoring data using the T-Test. The results show that there is a significant difference in platelet levels between the treatment and control groups. EVOO helps prevent preeclampsia by stabilizing the platelet levels of pregnant women.